Efficacy of Danlou tablets in patients with acute coronary syndrome undergoing percutaneous coronary intervention: a multicenter prospective cohort study - Cai, Yajie; Yang, Qiaoning; Xi, Ruixi; Yang, Furong; Gu, Feng; Zhao, Yang; Guo, Ming; Dong, Guoju; Gao, Zhuye; Fu, Changgeng; Wang, Peili; Du, Jianpeng; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Danlou tablets (DLTs) have been widely used to treat coronary heart disease in China. However, the benefits associated with DLT for patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) in routine practice require further investigation.Purpose: To investigate the effectiveness of DLT in patients with ACS undergoing PCI. Methods: This multicenter prospective cohort study for patients with ACS undergoing PCI was conducted in 40 centers in mainland China from February 2012 to December 2018. This trial is registered under ChiCTR-OOC-14005552. Patients were assigned to either the DLT group or the conventional medicine (CM) group based on whether they used DLT prior to enrollment. The Cox proportional hazards regression model was used to analyze the independent effect of DLT on primary and secondary endpoints. Propensity score matching (PSM) analyses were performed to mitigate bias. Survival estimation was performed using Kaplan–Meier survival curves and log-rank tests in the PSM cohort, and landmark analyses were used for further evaluation of primary and secondary endpoints. Subgroup analyses and interactions confirmed the robustness of the findings. Linear mixed effects models were used to assess the QOL. Results: Overall, 936 patients were enrolled in this cohort study, of whom 875 completed follow-up. The primary and secondary endpoints had no significantly difference between the DLT and CM groups after Cox proportional hazards models. However, landmark analysis showed significant benefit in the primary endpoint for the DLT group after 200 days (hazard ratio [HR] 0.46, 95% confidence interval [CI] 0.22–0.93, P = 0.03). Landmark analysis also showed a significant benefit in the secondary endpoint in the DLT group within 200 days (HR 0.33, 95% CI 0.15–0.73, P = 0.006). Moreover, DLT improves the SAQ summary score, and scores in the physical limitation, treatment satisfaction, and disease perception domains for patients with ACS undergoing PCI. Conclusions: DLT combined with conventional treatment reduced the risk of the primary endpoint after 200 days and the secondary endpoint within 200 days during the 3-year follow-up. Additionally, DLT can improve the QOL without adverse effects.